Regional geological subdivision of the Bohemian Massif on the territory of the Czech Republic (Report of the Working Group for Regional Geological Classification of the Bohemian Massif at the former Czechoslovak Stratigraphic Commission) - Chlupac,I.; Vrana,S. (Journal of the Czech Geological Society, 1994)
The progressing knowledge of geological history and structure of the Bohemian Massif on the territory of the Czech Republic results in increasing need of objective classification and terminology of geological units. Although a scheme of subdivisions and terminological principles was published in 1976, new data and views made a revision necessary.The former Czechoslovak Stratigraphic Commission initiated in 1991 the establishment of a working group which evaluated written comments of about 30 workers in regional geology of Bohemian Massif and prepared a new revised version of regional tectonostratigraphic subdivisions. This was later subject to discussions at several meetings and scientific seminars.The Working Group, composed of S. Cech, I. Chlupac, A. Dudek, M. Elias, V. Holub, J. Pesek, Z. Pouba, O. Shrbeny, J. Tyracek, J. Valecka, Z. Vejnar and J. Zapletal, submitted the final proposal in the second half of 1992, and after the expert evaluation made by J. Dvorak, J. Petranek and V. Zoubek, the Stratigraphic Commission approved the new scheme (June 17th, 1992).The Czech version was published in the Journal of Mineralogy and Geology vol. 37, No. 4 (1992). As the defined subdivisions are of general interest for many workers dealing with the geology of the Bohemian Massif, the English version is presented.